Status of Improved Fish Production Technology Adoption in Dhanusha District, Nepal - Paudel, Subodh; Chaulagain, Denisa; Chaudhary, Bijay Kumar; Shrestha, Susma; Chaulagain, Supriya; Singh, Abhishek; Kushwaha, Bijay Kumar; Gharti, Kamala (Journal of Agriculture and Resource Management, 2024)
The study was conducted in Dhanusha district of Madhesh province of Nepal to find out the social and demographic characteristics of farmers, available technologies for fish production, identification and adoption of available technologies, and major problems faced by farmers in the adoption of improved fish production technologies. 64 respondents were selected by simple random sampling method. Collected data were analyzed using SPSS 25.0 and MS-Excel. Various factors affecting the adoption of improved fish production technology were assessed using the chi-square test. It was found that fish farming was male-dominated in the area, and the mean family size was 5.88. Additionally, the majority of respondents (60.9%) had a pond size greater than 1 ha with a mean pond size of 1.33 ha. Farmers' mean age was 45.67 years. The major sources of information on fish farming were fellow fish farmers and training. The chi-square test showed a significant association between adoption level with educational level, fish farming experience, pond size, and fish farming training received. Technologies like stocking of ponds (89.1%), fish harvesting (87.5%), fish feeding (79.7%), maintenance of ponds (78.1%), site selection for ponds (75%), and pond construction (64.1%) were highly adopted by farmers. However, they had low adoption in post-harvest preservation and storage (4.7%). High feed costs, inadequate capital, and lack of technical knowledge were major problems in adopting improved fish production technologies.